2002
DOI: 10.1111/j.1365-2621.2002.tb11385.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Water Activity on the Stability to Oxidation of Spray‐Dried Encapsulated Orange Peel Oil Using Mesquite Gum (Prosopis Juliflora) as Wall Material

Abstract: Mesquite gum solutions (30% w/v) were used to emulsify orange peel oil in an oil-gum solids ratio of 0.25. Emulsions were spray dried in laboratory scale equipment. The powders were stored in a w (s) from 0.108 to 0.743 at 35 Њ Њ Њ Њ ЊC. Quantitative analysis of limonene oxide indicated that the sample at 0.628 showed a very good stability against oxidation after thirty d, without caking and stickiness occurring. At this water activity the system was within rubbery state, and the moisture content corresponded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
0
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(78 citation statements)
references
References 26 publications
(15 reference statements)
6
67
0
4
Order By: Relevance
“…For all of the equilibrium moisture content range the net integral entropy values were negative. Negative net integral entropy values were attributed to the existence of chemical adsorption and/or structural modifications of the absorbent The thermodynamic analysis of moisture sorption in dried foodstuffs has drawn interest because it provides a more thorough interpretation of the sorption isotherm phenomenon and helps to understood better the sorption mechanism (Beristain et al 2002). Thermodynamic parameters such as net isosteric heat, differential entropy, net integral enthalpy and entropy could be used to determine interactions of water and food substances and to provide information useful for assessing food processing operations such as drying, mixing and storage.…”
Section: Net Integral Enthalpy and Entropymentioning
confidence: 99%
See 1 more Smart Citation
“…For all of the equilibrium moisture content range the net integral entropy values were negative. Negative net integral entropy values were attributed to the existence of chemical adsorption and/or structural modifications of the absorbent The thermodynamic analysis of moisture sorption in dried foodstuffs has drawn interest because it provides a more thorough interpretation of the sorption isotherm phenomenon and helps to understood better the sorption mechanism (Beristain et al 2002). Thermodynamic parameters such as net isosteric heat, differential entropy, net integral enthalpy and entropy could be used to determine interactions of water and food substances and to provide information useful for assessing food processing operations such as drying, mixing and storage.…”
Section: Net Integral Enthalpy and Entropymentioning
confidence: 99%
“…The thermodynamic functions of water sorption in dried foodstuffs have drawn interest because it provides a more through interpretation of the sorption isotherm phenomenon and helps to understand better the sorption mechanism (Beristain et al 2002;Pérez-Alonzo et al 2006). The net isosteric heat of sorption can be used to estimate the energy requirements of drying and provides important information on the state of water in foodstuffs.…”
Section: Introductionmentioning
confidence: 99%
“…A secagem por spray drying tem sido aplicada a vários alimentos líquidos e pastosos, devido ao rápido contato dos mesmos com altas temperaturas, minimizando danos térmicos, além da alta produção e baixo custo em comparação com a liofilização 1,5,14,15,21,27,34 .…”
Section: Introductionunclassified
“…Succinylated waxy corn starch had the lowest values of surface oil. The high displayed stability may be attributed to good surface-active properties (ROMÁN-GUERRERO et al, 2009) of starch derivatives which possess hydrophobic groups that are accessible in short timescale, which enable them to adhere and spread out at the interface, thereby protecting newly formed droplets from aggregating or coalescing through steric stabilization and electrostatic stabilization mechanisms (DICKINSON, 2003). According to Risch and Reineccius (1988), this parameter is strongly associated with the emulsion droplet size, and low surface oil content is very important for providing storage stability to flavorings subject to oxidative present study, inlet air temperature of 180±1 °C and outlet air temperature of 100±5 °C resulted in high efficiency of d-limonene retention in all the wall materials evaluated.…”
Section: External Morphology Of the Microcapsulesmentioning
confidence: 99%
“…Carrillo-Navas et al (2011) reported moisture content values from 4.82 to 5.51% in microcapsules of gum Arabic-mesquite and gum-maltodextrin. Beristain, Azuara and Vernon-Carter (2002) reported 4.91% moisture content in microcapsules of orange peel with mesquite gum solutions as wall materials using spray drying.…”
Section: Retention Of Orange Peel Oil During Spray Dryingmentioning
confidence: 99%